Nanoparticles in Hormonal Regulation of the Female Reproductive System - Vandhana Vijayakumar; Thirumalaikumaran Rathinam; Sakthi Sanjana Deenadhayalan; Elizabeth Rani Edwin; Preethi Harikrishnan; Prathiba Balaji (Journal of Bio-X Research)
Nanoparticles (NPs) are increasingly recognized for their dual roles in both advancing and posing risks to female reproductive health. Owing to their small size and large surface area, NPs can interact with biological systems in ways that may lead to both therapeutic innovations and toxicological concerns. The impact of NPs on the female reproductive system highlights their potential to disrupt hormone signaling pathways and the hypothalamic–pituitary–gonadal axis, which are crucial for reproductive health. NPs have shown promise in targeted drug delivery systems, improving therapeutic outcomes for conditions such as endometriosis, polycystic ovary syndrome, and uterine leiomyoma. Advances in nanotechnology have facilitated the development of more sensitive diagnostic tools and innovative treatments, including NP-mediated drug delivery and hyperthermia. However, the accumulation of NPs in reproductive organs raises concerns about their potential toxicity, particularly in terms of oxidative stress, inflammation, and DNA damage. This review underscores the need for further research to fully understand the long-term effects of NPs on female reproductive health and to establish safe exposure limits. Additionally, the potential of NPs in gene therapy and tissue-targeted treatment offers a promising avenue for future clinical applications, with the possibility of revolutionizing the diagnosis and management of reproductive disorders.